2012
DOI: 10.1111/j.1746-1561.2012.00698.x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of School Policies to Prevent Youth Tobacco Use in Alabama

Abstract: Preparing smoke-free youth requires implementing and evaluating tobacco education in grades K-12 including use of model guidelines from federal agencies and professional organizations. Determining the focus of existing school tobacco policies is an initial step to encourage adoption of comprehensive policies to reduce youth use of tobacco. Youth health advocates may act together with school administrators and legislators to strengthen policies to be consistent with model guidelines for tobacco prevention and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…Stakeholder involvement was critical at every stage of the policymaking process, including policy formulation 23,24,40 , adoption 52,53 , implementation 46,47 , and evaluation 51 . Media pressure and engagement were highlighted as ways to increase civic support, awareness, education, youth advocacy, and stakeholder engagement 18,23,24,26,27,34,36,37,[54][55][56][57][58][59][60][61][62][63] . Civil society organizations can also help countries monitor and counter tobacco industry interference, and build capacity for implementing and evaluating smoke-free policies 23,24 .…”
Section: Civil Society Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…Stakeholder involvement was critical at every stage of the policymaking process, including policy formulation 23,24,40 , adoption 52,53 , implementation 46,47 , and evaluation 51 . Media pressure and engagement were highlighted as ways to increase civic support, awareness, education, youth advocacy, and stakeholder engagement 18,23,24,26,27,34,36,37,[54][55][56][57][58][59][60][61][62][63] . Civil society organizations can also help countries monitor and counter tobacco industry interference, and build capacity for implementing and evaluating smoke-free policies 23,24 .…”
Section: Civil Society Engagementmentioning
confidence: 99%
“…This study identified 78 studies that discussed compliance with smoke-free policies and 75 studies that discussed enforcement. Key factors identified in the literature as inhibiting smoke-free policy compliance include: a lack of awareness and training among stakeholders, limited government involvement in policy implementation and enforcement, lack of resources, negative attitudes and perceptions of smoke-free policies, and social and cultural norms 21,44,46,59,81,[89][90][91][92] . To combat these challenges, studies recommend educational efforts, stakeholder involvement, and taking action to address social norms 27,74,78,81,[93][94][95][96][97][98][99] .…”
Section: Policy Compliance and Enforcementmentioning
confidence: 99%